Lima Negara Bagian Terpenting dalam Negara Republik Indonesia Serikat (RIS) 1949-1950 - Irhas Fansuri Mursal; Lagut Bakaruddin (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2020)
This research aims to analyze a country which is highly calculated within the body of the United Republic of Indonesia. At the time of the formation of the United Republic of Indonesia (RIS) which consisted of 16 states, but not all of these countries were counted by the Netherlands or Indonesia, there were five countries which were greatly expanded during the RIS period in the State of East Sumatra, South Sumatra, Pasundan, The State of East Indonesia, and the Republic of Indonesia. This research uses the Historical research method which consists of four steps, namely: (1) Heuristics; (2) Criticism; (3) interpretation; (4) Historiography. The results of this research show that the causes of these five countries are considered very important in the body of the Republic of the United States of Indonesia, because of the vast territory, population density, and territory of the country.